Event-Free Survival Following Successful Percutaneous Intervention in Acute Myocardial Infarction Depends on Microvascular Perfusion. (June 2020) - Xie, Feng; Qian, Lijun; Goldsweig, Andrew; Xu, Di; Porter, Thomas R.
Abstract : Background: Although small trials have detected microvascular obstruction (MVO) with variable frequency following restoration of epicardial blood flow, the independent impact of abnormal microvascular perfusion (MVP) in predicting patient outcome following emergent percutaneous coronary intervention in acute ST-segment–elevation myocardial infarction is unknown. The study aims to determine the impact of abnormal MVP following successful epicardial recanalization in ST-segment–elevation myocardial infarction. Methods: MVP was analyzed by low mechanical index ultrasound imaging within 48 hours of emergent percutaneous coronary intervention in 297 patients with acute ST-segment–elevation myocardial infarction who had restoration of Thrombolysis in Myocardial Infarction grade 3 flow in the infarct vessel. Patients were divided into normal segmental replenishment (normal MVP) after high mechanical index impulses versus delayed replenishment but normal plateau intensity (delayed MVP) and both delayed replenishment and reduced plateau intensity (MVO by definition). Demographic variables, left ventricular ejection fraction change, and 5-year follow-up of death, recurrent myocardial infarction, and congestive heart failure were analyzed. Results: MVO was seen in 115 patients (39%), delayed MVP in 124 (42%), and normal MVP in 58 patients (19%). Patients with MVO had significant lower left ventricular ejection fraction change (39±12%) at hospital discharge compared with delayed MVP (50±10%; P =0.003) and normal MVP (57±8%; P <0.0001) groups. The MVO group also did not have an improvement in left ventricular ejection fraction change at 3-month follow-up (36±12% versus 37±13%; P =0.18). Both delayed MVP and MVO were independent predictors of adverse events at follow-up (hazard ratio, 21 [CI, 4–116]; P =0.001 and hazard ratio, 30 [CI, 5–183]; P <0.0001, respectively). Conclusions: Reduced or absent MVP following successful percutaneous coronary intervention in acute ST-segment–elevation myocardial infarction is common and associated with significantly worse outcome even with Thrombolysis in Myocardial Infarction 3 flow in the infarct vessel. Abstract : Supplemental Digital Content is available in the text.